THE FEDERAL TOBACCO CONTROL EFFORT (Tufts Archival Research Center, 2007)
Report summarizing federal tobacco control activities. Presents an organizational chart and summaries of activities grouped by cabinet-level department. Gives an overview of each office and describes tobacco control efforts. Explains how each addresses different aspects of tobacco control, with pro-tobacco bias.